Curricular orientations to real‐world contexts in mathematics. Issue 1 (2nd January 2016) - Smith, Cathy; Morgan, Candia
ABSTRACT: A common claim about mathematics education is that it should equip students to use mathematics in the 'real world'. In this paper, we examine how relationships between mathematics education and the real world are materialised in the curriculum across a sample of eleven jurisdictions. In particular, we address the orientation of the curriculum towards application of mathematics, the ways that real‐world contexts are positioned within the curriculum content, the ways in which different groups of students are expected to engage with real‐world contexts, and the extent to which high‐stakes assessments include real‐world problem solving. The analysis reveals variation across jurisdictions and some lack of coherence between official orientations towards use of mathematics in the real world and the ways that this is materialised in the organisation of the content for students.